Piezoelectric SiC ceramic membrane with in-situ self-cleaning function and application thereof
By loading UiO-66-NH2 (Hf) on the SiC ceramic membrane and modifying hydroxyl functional groups, combined with hydraulic pulse pressure, the membrane pollution problem in oil-water separation is solved, realizing in-situ self-cleaning and efficient oil-water Separation avoids external power dependence and high energy consumption.
Patent Information
- Application Number
- CN202411092602.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing SiC ceramic membranes are prone to membrane contamination due to accumulation of oil droplets during oil-water separation. Traditional modification methods cannot effectively solve the membrane contamination problem, and there are problems such as external power dependence and high energy consumption.
The SiC ceramic membrane was modified by UiO-66-NH2(Hf)-loaded hydroxyl functional groups, and UiO-66-NH2(Hf) was loaded on the base film by hydrothermal method, and combined with hydraulic pulse pressure to achieve oil droplet demulsification on the membrane surface and Self-cleaning to avoid external power irritation.
It realizes in-situ self-cleaning of the membrane, improves oil-water separation performance and anti-pollution ability, reduces the risk of membrane pollution, does not require external equipment and chemical cleaning, and is generally green and environmentally friendly.
Smart Images

Figure CN119113825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a piezoelectric SiC ceramic membrane and applications thereof, in particular to a piezoelectric SiC ceramic membrane with an in-situ self-cleaning function and applications thereof in oil-water separation, belonging to the technical field of piezoelectric SiC ceramic membranes. Background Art
[0002] Industrial progress has not only led to a sharp increase in energy demand, but also resulted in the discharge of large quantities of oily wastewater. Oil removal from oily wastewater has been a major concern worldwide due to its difficulty in separation and environmental hazards. Oil droplets in oily wastewater can be categorized as free oil (>150 μm), dispersed oil (20 to 150 μm), and emulsified oil (<20 μm) based on their diameter. Traditional methods for removing oil from oily wastewater include coagulation, gravity separation, and ozone oxidation. However, these methods are not able to effectively separate the emulsified oil from oily wastewater.
[0003] Membrane separation technology is a novel technique that utilizes the selectivity of membranes and the application of pressure to separate, concentrate, purify, and refine different components in a liquid. In recent years, membrane separation technology has become a highly effective method for removing emulsified oil from oily wastewater. As the core of membrane separation technology, the performance of the membrane itself has a significant impact on the effectiveness of membrane separation.
[0004] SiC ceramic membranes have excellent chemical and thermal stability, low energy consumption, and high removal efficiency, and are currently widely used in the field of oil-water separation. However, the current mainstream oil-water separation membrane technology is based on the principle of size screening. In the absence of demulsification, oil droplets will inevitably accumulate on the membrane surface, causing membrane fouling during the oil-water separation process. This requires the oil-water separation process to be shut down and the contaminated membrane to be cleaned with chemical cleaning agents, seriously affecting the oil-water separation efficiency. Therefore, solving this type of membrane fouling problem is crucial to improving oil-water separation efficiency. Studies have reported that constructing special wettability on the membrane surface, for example, constructing a super-hydrophilic surface on the membrane surface, can reduce the tendency of pollutants to adhere to the membrane. Therefore, static modification of the surface of SiC ceramic membranes is currently a commonly used method to reduce membrane fouling.
[0005] Patent CN114315363B discloses a method for regulating the pore structure and surface properties of silicon carbide membranes in one step. The patent first thoroughly mixes SiC powder with a sintering aid, and then synergistically regulates the pore structure and surface wettability of the SiC membrane by controlling the molding pressure and sintering conditions. Although the SiC membrane prepared in this patent has high bending strength and pure water permeability, and has broad application prospects in the fields of oil-water separation and emulsion preparation, when the SiC membrane in this patent is used for oil-water separation, even without demulsification, concentrated oil droplets will inevitably form on the membrane surface, which will still cause serious membrane contamination problems.
[0006] Patent CN113926321A discloses a method for preparing and using a contamination-resistant ceramic membrane. This patent describes a porous ceramic support using alumina powder as the raw material. Ferric chloride is added to 100°C water and heated to produce a ferric hydroxide sol. After cooling, the ferric hydroxide sol is mixed with a 300 nm alumina membrane-forming solution. The membrane-forming solution is then applied to the surface of the ceramic support, followed by air-drying, oven-baking, calcination, and natural cooling to produce an asymmetric membrane. This patent involves constructing a super-hydrophilic surface coating on the membrane surface. While this effectively improves the hydrophilicity of the separation membrane, thereby reducing the tendency of contaminants to adhere to or adsorb onto the membrane, it only reduces the membrane's fouling rate, and the membrane will ultimately become contaminated.
[0007] Patent CN115672060A discloses a method for preparing a catalytic ceramic membrane with a super-wetting surface and its application in oil-containing emulsion wastewater. The ceramic membrane prepared in this patent is loaded with nano-sized Fe₃O₄, exhibiting both a super-wetting surface and a Fenton-like catalytic effect. It exhibits excellent oil-water separation performance, as well as excellent anti-pollution and self-cleaning properties. However, this patent incorporates catalytically active transition metal oxides into the membrane separation layer, which not only causes melt leakage during the high-temperature preparation process but also creates numerous defects on the membrane material surface, seriously affecting the membrane's filtration performance.
[0008] Patent CN115121232B discloses a titanium dioxide self-cleaning membrane and its preparation method and application. The patent first uses tea polyphenol 6-acetamido-β-cyclodextrin to modify the polymer microporous membrane with amino groups and vacancy seed phase points, and then uses the solution-gel method to achieve in-situ mineralization and vacancy in-situ complexation of tetrabutyl titanate on the surface of the microporous membrane to prepare a structurally stable nano-titanium dioxide composite self-cleaning membrane for efficient adsorption of antimony. Although the titanium dioxide self-cleaning membrane in this patent can effectively remove humic acid and Sb in wastewater, it can also effectively remove humic acid and Sb in wastewater. 3+ , and also has a self-cleaning function, but the TiO2 in the titanium dioxide self-cleaning film is an amphoteric oxide, which is easily corroded in strong acid and strong alkali systems and has unstable performance, resulting in the titanium dioxide self-cleaning film still being limited in engineering practice.
[0009] Patent CN113842784A discloses a method for preparing and applying a pollution-resistant silicon carbide ceramic membrane. This patent utilizes a silicon carbide ceramic sheet or tube as a carrier, directly synthesizing a layer of silicon carbide nanowire membrane in situ via chemical vapor deposition (CVD) on the carrier, effectively enhancing the bonding strength between the silicon carbide nanowires and the carrier. While this patent enhances the material's pollution resistance by using silicon carbide nanowires as the functional layer material to create a network structure with interlaced pores, thereby reducing the adhesion or adsorption of pollutants on the membrane surface to a certain extent, the modification described in this patent only reduces the membrane fouling rate, ultimately still leading to membrane fouling issues.
[0010] In summary, the method of static modification of the surface of SiC ceramic membranes cannot effectively solve the problem of membrane fouling. Therefore, some researchers have proposed demulsifying the emulsified oil to reduce membrane fouling. Electrochemical demulsification is a common method for demulsifying emulsified oil. Electrochemical demulsification refers to the uneven polarization and deformation of stable surface-charged oil droplets under the drive of a high electric field, resulting in the effective thinning and rupture of the intermediate liquid film. Electroresponsive membrane materials usually use external stimulus-responsive materials as surface coatings or membranes, which can modify the electric field on the membrane surface in real time, thereby achieving demulsification. Therefore, there are currently reports on the use of electroresponsive membrane materials for oil / water separation or emulsion demulsification.
[0011] Patent CN106853340B discloses an asymmetric in-situ ultrasonic anti-pollution membrane with a piezoelectric material as a support and its preparation method. This patent uses piezoelectric ceramic powder as raw material to prepare a ceramic support with a porous structure, and prepares a porous inorganic separation layer on its surface. The wet membrane is air-dried, baked, calcined, and naturally cooled to prepare an asymmetric membrane structure, and then a non-stacked in-situ ultrasonic anti-pollution membrane is obtained by high-voltage polarization. When the anti-pollution membrane prepared by this patent is used for oil-water separation, it can generate mechanical vibration, which uses mechanical vibration to slow down the accumulation of pollutants on the membrane surface, thereby playing an anti-pollution role. However, the anti-pollution membrane prepared by this patent needs to be equipped with an additional external power supply when in use. The anti-pollution membrane can only generate ultrasonic vibration in situ under the stimulation of the external power supply, converting electrical energy into mechanical energy, thereby suppressing membrane pollution. This not only increases unnecessary power consumption and increases the complexity of the oil-water separation system, but also leads to poor safety of the oil-water separation process. Summary of the Invention
[0012] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a piezoelectric SiC ceramic membrane with in-situ self-cleaning function and its application in oil-water separation.
[0013] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:
[0014] A piezoelectric SiC ceramic membrane with an in-situ self-cleaning function is composed of a SiC ceramic membrane as a base membrane and UiO-66-NH2(Hf) loaded on the base membrane.
[0015] In one embodiment, the piezoelectric SiC ceramic film has a UiO-66-NH2(Hf) loading of 65.12 to 86.15 g / m 2 .
[0016] In one embodiment, the base membrane is a SiC ceramic membrane modified with hydroxyl functional groups, and the SiC ceramic membrane modified with hydroxyl functional groups is obtained by sequentially subjecting a clean SiC ceramic membrane to oxidation treatment and acidification treatment.
[0017] In a preferred embodiment, the preparation of the SiC ceramic membrane modified with hydroxyl functional groups comprises the following operations:
[0018] First, the SiC ceramic diaphragm is cleaned and dried to obtain a clean SiC ceramic diaphragm; then, the clean SiC ceramic diaphragm is oxidized in air or oxygen atmosphere to obtain a slightly oxidized diaphragm; then, the slightly oxidized diaphragm is placed in a strong acid solution for acidification treatment, and finally, the diaphragm is taken out, cleaned, and dried to obtain a SiC ceramic membrane modified with hydroxyl functional groups.
[0019] In a preferred embodiment, the oxidation treatment is to place the clean SiC ceramic diaphragm in a muffle furnace and perform oxidation treatment at 900°C to 1200°C for 60 to 150 minutes in air or oxygen atmosphere to obtain the micro-oxidation diaphragm.
[0020] In a preferred embodiment, the acid treatment is to immerse the micro-oxidation membrane in a strong acidic solution for 20 to 30 hours, remove the membrane, wash the membrane with deionized water until it is neutral, and dry it to obtain the SiC ceramic membrane modified with hydroxyl functional groups, wherein the strong acidic solution is a mixed solution of concentrated hydrochloric acid: concentrated nitric acid in a volume ratio of (8 to 12):1.
[0021] In one embodiment, the piezoelectric SiC ceramic film is obtained by hydrothermally reacting a base film and a crystal growth solution, and loading UiO-66-NH2(Hf) on the base film by a hydrothermal method.
[0022] A preferred solution is to load UiO-66-NH2(Hf) on a base film by a hydrothermal method to obtain a piezoelectric SiC ceramic film, including the following operations:
[0023] a) preparing a primary crystal growth solution of hafnium chloride: 2-aminoterephthalic acid: N,N-dimethylformamide: water: acetic acid in a ratio of 1:1:500:10:1, placing a base film in the primary crystal growth solution, and reacting at 110° C. to 130° C. for 12 to 24 hours. After the reaction is completed, removing the film, washing, and drying to obtain a primary loaded film;
[0024] b) hafnium chloride: 2-aminoterephthalic acid: N,N-dimethylformamide: water: acetic acid are prepared into a secondary crystal growth solution in a molar ratio of (1-2):(1-2):500:10:1, the prepared primary load membrane is placed in the secondary crystal growth solution, and the reaction is carried out at 110° C. to 130° C. for 20 to 30 hours. After the reaction is completed, the membrane is removed, cleaned, and dried to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
[0025] In a preferred embodiment, in step a), after the reaction is completed, the membrane is removed, first washed with N, N-dimethylformamide solution, then cleaned with anhydrous ethanol, and then vacuum dried at 60°C to 100°C to obtain the primary loaded membrane.
[0026] In a preferred embodiment, in step b), after the reaction is completed, the diaphragm is removed and placed in a mixed solution of N, N-dimethylformamide and concentrated hydrochloric acid in a volume ratio of (30-50):1. The diaphragm is soaked at 60°C to 100°C for 8-12 hours and then removed. The diaphragm is then soaked and cleaned with an ethanol solution and finally vacuum dried at 60°C to 100°C to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
[0027] An application of a piezoelectric SiC ceramic membrane with in-situ self-cleaning function in oil-water separation includes the following operations:
[0028] A piezoelectric SiC ceramic membrane is placed in a filter tank as a filter membrane; oily wastewater containing emulsified oil with an initial turbidity of C0 is passed into the filter tank. During the process of passing the oily wastewater into the filter tank, the hydraulic pressure of the oily wastewater is first quickly increased from 0 bar to 2 bar within 1 to 3 seconds, and then the hydraulic pressure is maintained at 2 bar for 50 to 70 seconds, and then the hydraulic pressure is returned to 0 bar within 1 to 3 seconds. In this way, a periodic cycle is performed according to the mode of pressure increase, pressure maintenance, and pressure reduction; the oily wastewater is filtered through the filter membrane, and the turbidity of the obtained filtrate is detected by a turbidity meter to obtain the turbidity C1 of the oily wastewater after membrane separation; the retention rate R of the filter membrane for the oily wastewater is calculated according to the formula R = ((C0-C1) / C0)×100%.
[0029] Compared with the prior art, the present invention has the following significant beneficial effects:
[0030] The piezoelectric SiC ceramic membrane provided by the present invention has excellent membrane separation performance and self-cleaning ability. When used for oil-water separation, it can not only effectively remove emulsified oil in oily wastewater, but also convert hydraulic pulse pressure into electrical activity. During the oil-water separation process, no external power supply is required. Only by periodically changing the hydraulic pressure of the oily wastewater, the oil droplets on the membrane surface can be demulsified and the accumulation of oil droplets on the membrane surface can be prevented, thereby playing an anti-pollution role and realizing in-situ self-cleaning of the membrane. No external anti-pollution equipment and chemical cleaning reagents are required, and membrane pollution can be prevented and controlled in the long term without stopping work and affecting production. In addition, the piezoelectric SiC ceramic membrane of the present invention is a membrane in which UiO-66-NH2(Hf) is loaded on the SiC ceramic membrane. The overall structure is green and environmentally friendly, easy to degrade, and will not cause secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Photos of the SiC ceramic diaphragm (a) without oxidation and acid pretreatment, the prepared SiC ceramic membrane modified with hydroxyl functional groups (b), and the piezoelectric SiC ceramic membrane (c) used in Example 1 of the present invention;
[0032] Figure 2 This is a surface electron microscope image of the SiC ceramic diaphragm used in Example 1 of the present invention without oxidation and acid pretreatment;
[0033] Figure 3 This is a surface electron micrograph of the SiC ceramic membrane modified with hydroxyl functional groups prepared in Example 1 of the present invention;
[0034] Figure 4 This is a surface electron microscope image of the piezoelectric SiC ceramic film prepared in Example 1 of the present invention;
[0035] Figure 5 This is a cross-sectional electron microscope image of the piezoelectric SiC ceramic film prepared in Example 1 of the present invention;
[0036] Figure 6 1 is a pore size distribution diagram of the SiC ceramic diaphragm without oxidation and acid pretreatment and the prepared piezoelectric SiC ceramic membrane used in Example 1 of the present invention;
[0037] Figure 7 This is a piezoelectric signal diagram of the SiC ceramic diaphragm used in Example 1 of the present invention without oxidation and acid pretreatment;
[0038] Figure 8 Graph showing the piezoelectric signal of the piezoelectric SiC ceramic film prepared in Example 1 of the present invention;
[0039] Figure 9 This is a surface electron microscope image of the piezoelectric SiC ceramic film prepared in Example 2 of the present invention;
[0040] Figure 10 This is a surface electron microscope image of the piezoelectric SiC ceramic film prepared in Example 3 of the present invention;
[0041] Figure 11 This is a surface electron microscope image of the comparative piezoelectric SiC ceramic film prepared in Comparative Example 2 of the present invention;
[0042] Figure 12 This is a flow chart of the oil-water separation performance test in the present invention;
[0043] Figure 13 Photos of the oily wastewater (a) used in the oil-water separation performance test of the present invention, the filtrate obtained by filtering the oily wastewater with the piezoelectric SiC ceramic membrane of Example 1 (b), the filtrate obtained by filtering the oily wastewater with the comparative piezoelectric SiC ceramic membrane of Comparative Example 1 (c), and the filtrate obtained by filtering the oily wastewater with the original SiC membrane (d);
[0044] Figure 14 This is a test diagram of the in-situ self-cleaning performance of the piezoelectric SiC ceramic film prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] The technical scheme of the present invention is further described in detail and completely below with reference to the examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the invention. The experimental methods in the following examples, for which specific conditions are not specified, are generally carried out under conventional conditions or as recommended by the manufacturer.
[0046] Example 1
[0047] 1) First, the SiC ceramic diaphragm is cleaned and dried to obtain a clean SiC ceramic diaphragm; then, the clean SiC ceramic diaphragm is placed in a muffle furnace and oxidized at 1100° C. for 120 minutes in an air atmosphere (to form a trace amount of silicon dioxide on the substrate surface) to obtain a slightly oxidized diaphragm; finally, the slightly oxidized diaphragm is immersed in a strong acidic solution for 24 hours (to form Si-OH groups on the silicon dioxide on the substrate surface), the diaphragm is removed, and the diaphragm is washed with deionized water until neutral, and dried to obtain a SiC ceramic membrane modified with hydroxyl functional groups, wherein the strong acidic solution is a mixed solution of concentrated hydrochloric acid:concentrated nitric acid in a volume ratio of 10:1;
[0048] 2) preparing a primary crystal growth solution of hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid at a molar ratio of 1:1:500:10:1, adding the primary crystal growth solution to a reaction kettle, placing the hydroxyl functional group-modified SiC ceramic membrane obtained in step 1) in the primary crystal growth solution, and reacting at 120° C. for 24 hours. After the reaction is completed, removing the membrane, first washing it with N, N-dimethylformamide solution, then washing it with anhydrous ethanol, and then drying it under vacuum at 60° C. overnight to obtain a primary loaded membrane;
[0049] 3) hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid in a molar ratio of 1.5:1.5:500:10:1 was prepared into a secondary crystal growth solution, the secondary crystal growth solution was added to a reactor, the primary load membrane prepared in step 2) was placed in the secondary crystal growth solution, and reacted at 120° C. for 24 hours. After the reaction, the membrane was removed and placed in a mixed solution of N, N-dimethylformamide: concentrated hydrochloric acid in a volume ratio of 40:1. The membrane was soaked at 80° C. for 10 hours (to clean the oligomers generated during the reaction) and then removed. The membrane was then soaked and cleaned with an ethanol solution and finally dried overnight under vacuum at 60° C. to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
[0050] Figure 1 These are actual photos of the SiC ceramic diaphragm (a) without oxidation and acid pretreatment, the prepared SiC ceramic membrane modified with hydroxyl functional groups (b), and the piezoelectric SiC ceramic membrane (c) used in this embodiment; it can be seen from the figure that UiO-66-NH2(Hf) is successfully loaded on the surface of the piezoelectric SiC ceramic membrane (c). Since UiO-66-NH2(Hf) is light yellow, the color of the piezoelectric SiC ceramic membrane (c) is yellower than that of the SiC ceramic membrane modified with hydroxyl functional groups (b).
[0051] Figure 2 This is a surface electron microscope image of the SiC ceramic diaphragm used in this embodiment without oxidation and acid pretreatment; Figure 3 Surface electron micrograph of the SiC ceramic film modified with hydroxyl functional groups prepared in this embodiment; Figure 2 and Figure 3 It can be seen that both the SiC ceramic membrane without oxidation and acid pretreatment and the SiC ceramic membrane modified with hydroxyl functional groups have porous structures.
[0052] Figure 4 This is a surface electron microscope image of the piezoelectric SiC ceramic film prepared in this embodiment; Figure 5 is a cross-sectional electron microscope image of the piezoelectric SiC ceramic film prepared in this embodiment; Figure 4 and Figure 5It can be seen that UiO-66-NH2(Hf) is successfully loaded on the surface of the SiC ceramic film. After testing, the loading amount of UiO-66-NH2(Hf) in the piezoelectric SiC ceramic film prepared in this embodiment is 74.45 g / m 2 .
[0053] Figure 6 This is the pore size distribution diagram of the SiC ceramic diaphragm without oxidation and acid pretreatment and the prepared piezoelectric SiC ceramic membrane used in this embodiment. It can be seen from the figure that the initial SiC ceramic diaphragm has a membrane pore size of about 0.7μm, which is too large to meet the needs of oil-water separation, while the prepared piezoelectric SiC ceramic membrane has a membrane pore size of about 0.4μm, indicating that after UiO-66-NH2(Hf) is loaded on the surface of the SiC ceramic membrane, the membrane pore size becomes smaller, which can meet the needs of oil-water separation.
[0054] Figure 7 : is a piezoelectric signal diagram of the SiC ceramic diaphragm used in this embodiment without oxidation and acid pretreatment; Figure 8 This is a piezoelectric signal diagram of the piezoelectric SiC ceramic film prepared in this embodiment; it can be seen from the figure that the SiC ceramic diaphragm used in this embodiment has no piezoelectric signal and does not have piezoelectric performance, while the prepared piezoelectric SiC ceramic film has a pulsed piezoelectric signal and has piezoelectric performance, indicating that the present invention can prepare a ceramic film with piezoelectric performance by loading UiO-66-NH2(Hf) on a SiC ceramic film.
[0055] Example 2
[0056] 1) First, the SiC ceramic diaphragm is cleaned and dried to obtain a clean SiC ceramic diaphragm; then, the clean SiC ceramic diaphragm is placed in a muffle furnace and oxidized at 1100° C. for 120 minutes in an air atmosphere (to form a trace amount of silicon dioxide on the substrate surface) to obtain a slightly oxidized diaphragm; finally, the slightly oxidized diaphragm is immersed in a strong acidic solution for 24 hours (to form Si-OH groups on the silicon dioxide on the substrate surface), the diaphragm is removed, and the diaphragm is washed with deionized water until neutral, and dried to obtain a SiC ceramic membrane modified with hydroxyl functional groups, wherein the strong acidic solution is a mixed solution of concentrated hydrochloric acid:concentrated nitric acid in a volume ratio of 10:1;
[0057] 2) preparing a primary crystal growth solution of hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid at a molar ratio of 1:1:500:10:1, adding the primary crystal growth solution to a reaction kettle, placing the hydroxyl functional group-modified SiC ceramic membrane obtained in step 1) in the primary crystal growth solution, and reacting at 120° C. for 24 hours. After the reaction is completed, removing the membrane, first washing it with N, N-dimethylformamide solution, then washing it with anhydrous ethanol, and then drying it under vacuum at 60° C. overnight to obtain a primary loaded membrane;
[0058] 3) hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid in a molar ratio of 1:1:500:10:1 was prepared into a secondary crystal growth solution, the secondary crystal growth solution was added to a reactor, the primary load membrane prepared in step 2) was placed in the secondary crystal growth solution, and reacted at 120° C. for 24 hours. After the reaction, the membrane was removed and placed in a mixed solution of N, N-dimethylformamide: concentrated hydrochloric acid in a volume ratio of 40:1. The membrane was soaked at 80° C. for 10 hours (to clean the oligomers generated during the reaction) and then removed. The membrane was then soaked and cleaned with an ethanol solution and finally dried overnight under vacuum at 60° C. to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
[0059] Figure 9 The surface electron microscope image of the piezoelectric SiC ceramic film prepared in this embodiment shows that UiO-66-NH2(Hf) is successfully loaded on the surface of the SiC ceramic film. The test shows that the loading amount of UiO-66-NH2(Hf) in the piezoelectric SiC ceramic film prepared in this embodiment is 65.12 g / m 2 .
[0060] Example 3
[0061] 1) First, the SiC ceramic diaphragm is cleaned and dried to obtain a clean SiC ceramic diaphragm; then, the clean SiC ceramic diaphragm is placed in a muffle furnace and oxidized at 1100° C. for 120 minutes in an air atmosphere (to form a trace amount of silicon dioxide on the substrate surface) to obtain a slightly oxidized diaphragm; finally, the slightly oxidized diaphragm is immersed in a strong acidic solution for 24 hours (to form Si-OH groups on the silicon dioxide on the substrate surface), the diaphragm is removed, and the diaphragm is washed with deionized water until neutral, and dried to obtain a SiC ceramic membrane modified with hydroxyl functional groups, wherein the strong acidic solution is a mixed solution of concentrated hydrochloric acid:concentrated nitric acid in a volume ratio of 10:1;
[0062] 2) preparing a primary crystal growth solution of hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid at a molar ratio of 1:1:500:10:1, adding the primary crystal growth solution to a reaction kettle, placing the hydroxyl functional group-modified SiC ceramic membrane obtained in step 1) in the primary crystal growth solution, and reacting at 120° C. for 24 hours. After the reaction is completed, removing the membrane, first washing it with N, N-dimethylformamide solution, then washing it with anhydrous ethanol, and then drying it under vacuum at 60° C. overnight to obtain a primary loaded membrane;
[0063] 3) hafnium chloride: 2-aminoterephthalic acid: N, N-dimethylformamide: water: acetic acid in a molar ratio of 2:2:500:10:1 was prepared into a secondary crystal growth solution, the secondary crystal growth solution was added to a reactor, the primary load membrane prepared in step 2) was placed in the secondary crystal growth solution, and reacted at 120° C. for 24 hours. After the reaction, the membrane was removed and placed in a mixed solution of N, N-dimethylformamide: concentrated hydrochloric acid in a volume ratio of 40:1. The membrane was soaked at 80° C. for 10 hours (to clean the oligomers generated during the reaction) and then removed. The membrane was then soaked and cleaned with an ethanol solution and finally dried overnight under vacuum at 60° C. to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
[0064] Figure 10 The surface electron microscope image of the piezoelectric SiC ceramic film prepared in this embodiment shows that UiO-66-NH2(Hf) is successfully loaded on the surface of the SiC ceramic film. The test shows that the loading amount of UiO-66-NH2(Hf) in the piezoelectric SiC ceramic film prepared in this embodiment is 86.15 g / m 2 .
[0065] Comparative Example 1
[0066] Comparative Example 1 follows the same procedures as Example 1, except that the hydroxyl-modified SiC ceramic membrane obtained in step 1) undergoes only a primary growth reaction, without undergoing a secondary growth reaction, and the crystal growth solution used in the primary growth reaction is a mixture of hafnium chloride: 2-aminoterephthalic acid: N,N-dimethylformamide: water: acetic acid in a molar ratio of 1.5:1.5:500:10:1.
[0067] Comparative Example 2
[0068] The steps of Comparative Example 2 are the same as those of Example 1, except that the acidic solution used in the acid treatment is a mixed solution of concentrated sulfuric acid: hydrogen peroxide in a volume ratio of 1:3.
[0069] Figure 11 The surface electron microscope image of the comparative piezoelectric SiC ceramic film prepared in this comparative example is Figure 11 It can be seen that the UiO-66-NH2(Hf) particle loading on the surface of the SiC ceramic membrane is sparse and uneven, and the preparation of the piezoelectric SiC ceramic membrane has failed. This shows that the choice of strong acid solution used in the acid treatment has an important influence on the pretreatment results of the SiC ceramic membrane and has an important influence on the subsequent UiO-66-NH2(Hf) loading.
[0070] Oil-water separation performance test
[0071] The piezoelectric SiC ceramic membranes prepared in Examples 1-3 of the present invention, the comparative piezoelectric SiC ceramic membrane prepared in Comparative Example 1 of the present invention, and the SiC ceramic membrane used in the present invention without oxidation and acid pretreatment (hereinafter referred to as the original SiC membrane) were respectively used in the oil-water separation experiment to test the oil-water separation performance of the membranes. The test process is as follows: Figure 12 The test results are shown in Table 1 and Figure 13 As shown:
[0072] Combine Figure 12 As shown, the piezoelectric SiC ceramic membranes prepared in Examples 1-3 of the present invention, the comparative piezoelectric SiC ceramic membranes prepared in Comparative Example 1 of the present invention, and the SiC ceramic membranes used in the present invention that have not been oxidized and acid pretreated (referred to as SiC original membranes) are respectively placed in a filter tank as filter membranes; oily wastewater containing emulsified oil with an initial turbidity of C0 (C0 is specifically 2500 ppm) is passed into the filter tank (specifically: the oily wastewater is pumped into the filter tank by a peristaltic pump, and the peristaltic pump is provided with a pressure gauge for detecting the hydraulic pressure of the oily wastewater). During the process of passing the oily wastewater into the filter tank, the hydraulic pressure of the oily wastewater is first rapidly increased from 0 bar to 2 bar within 1 to 3 seconds, and then the hydraulic pressure is maintained at 2 bar for 60 seconds, and then the hydraulic pressure is returned to 0 bar within 1 to 3 seconds (specifically: the flow rate of the peristaltic pump is increased, the hydraulic pressure of the oily wastewater in the peristaltic pump pipeline is rapidly increased from 0 bar to 2 bar within 1 to 3 seconds, and then this flow rate is maintained for 60 seconds, so that the hydraulic pressure can be returned to 0 bar within 1 to 3 seconds). bar is maintained for 60 seconds, and then the peristaltic pump is reversed to pump out the oily wastewater in the peristaltic pump pipeline in the reverse direction, so that the hydraulic pressure of the oily wastewater in the peristaltic pump pipeline returns to 0 bar within 1 to 3 seconds). In this way, a periodic cycle is performed according to the pressure increase, pressure maintenance, and pressure reduction mode (this mode is referred to as the pulse pressure mode); the oily wastewater is filtered through the filter membrane, and the turbidity of the obtained filtrate is detected by a turbidity meter to obtain the turbidity C1 of the oily wastewater after membrane separation; the retention rate R of the filter membrane for the oily wastewater is calculated according to the formula R = ((C0-C1) / C0) × 100%.
[0073] Table 1 Oil-water separation performance test data
[0074]
[0075] From the results shown in Table 1, it can be seen that when the piezoelectric SiC ceramic membrane prepared by the present invention is used for oil-water separation of oily wastewater, not only the rejection rate of the oily wastewater is higher than 99%, but also the turbidity of the obtained filtrate is lower than 10NTU, and a clear filtrate can be obtained, indicating that the piezoelectric SiC ceramic membrane prepared by the present invention can effectively remove the emulsified oil in the oily wastewater when performing oil-water separation treatment on the oily wastewater, and has good oil-water separation performance; when the comparative piezoelectric SiC ceramic membrane in Comparative Example 1 is used for oil-water separation treatment of the oily wastewater, although the oily wastewater The retention rate is higher than 95%, but the turbidity of the obtained filtrate is higher than 30NTU, and the turbidity of the filtrate does not meet the requirements, indicating that the comparative piezoelectric SiC ceramic membrane in Comparative Example 1 has poor oil-water separation performance for oily wastewater and cannot effectively remove the emulsified oil in the oily wastewater; when the SiC original membrane performs oil-water separation treatment on the oily wastewater, not only is the retention rate of the oily wastewater lower than 90%, but the turbidity of the obtained filtrate is higher than 97NTU, indicating that the oil-water separation performance of the SiC original membrane for oily wastewater is very poor, and the emulsified oil in the oily wastewater can hardly be removed.
[0076] Figure 13 The following are photos of the oily wastewater (a) used in the oil-water separation performance test, the filtrate obtained by filtering the oily wastewater with the piezoelectric SiC ceramic membrane in Example 1 (b), the filtrate obtained by filtering the oily wastewater with the comparative piezoelectric SiC ceramic membrane in Comparative Example 1 (c), and the filtrate obtained by filtering the oily wastewater with the original SiC membrane (d). Figure 13 It can be seen that when used for oil-water separation test, the piezoelectric SiC ceramic membrane prepared in Example 1 of the present invention can obtain a clear and transparent filtrate, while the comparative piezoelectric SiC ceramic membrane and the original SiC membrane of Comparative Example 1 can only obtain turbid filtrate, indicating that the piezoelectric SiC ceramic membrane prepared in Example 1 can effectively remove emulsified oil in oily wastewater and has good oil-water separation performance, while the comparative piezoelectric SiC ceramic membrane and the original SiC membrane of Comparative Example 1 cannot effectively remove emulsified oil in oily wastewater and have poor oil-water separation performance.
[0077] Comprehensive Table 1 and Figure 13 It can be seen that loading UiO-66-NH2(Hf) on the SiC ceramic membrane can effectively improve the oil-water separation performance of the membrane, and the oil-water separation performance of the membrane prepared by loading UiO-66-NH2(Hf) twice on the SiC ceramic membrane using the double growth method is better.
[0078] In-situ self-cleaning performance test
[0079] The piezoelectric SiC ceramic film prepared in Example 1 was used as a test object to test its in-situ self-cleaning performance. The specific test method is as follows:
[0080] The piezoelectric SiC ceramic membrane was used as a filter membrane in the filter tank. The oily wastewater was separated into oil and water using pulse pressure mode and non-pulse pressure mode respectively. The flux change of the piezoelectric SiC ceramic membrane during the oil-water separation process was recorded.
[0081] in,
[0082] The pulse pressure mode means that the hydraulic pressure of the oily wastewater is quickly increased from 0 bar to 2 bar within 1 to 3 seconds, the hydraulic pressure is then maintained at 2 bar for 60 seconds, and then the hydraulic pressure is returned to 0 bar within 1 to 3 seconds. In this way, the pressure is increased, maintained, and then reduced periodically.
[0083] The non-pulse pressure mode means that the hydraulic pressure of the oily wastewater is quickly increased from 0 bar to 2 bar within 1 to 3 seconds, and then the hydraulic pressure is maintained at a constant pressure of 2 bar.
[0084] Figure 14 The in-situ self-cleaning performance test diagram of the piezoelectric SiC ceramic film prepared in Example 1; Figure 14 It can be seen that the piezoelectric SiC ceramic membrane prepared in Example 1, when used for oil-water separation of oily wastewater, still has a certain flux after running for 50 minutes in the pulsed pressure mode, while the flux is almost reduced to 0 after running for 30 minutes in the non-pulsed pressure mode. This shows that when the piezoelectric SiC ceramic membrane of the present invention is used for water-oil separation, by controlling the hydraulic pulse changes of the oily wastewater, it can effectively prevent oil droplets from accumulating on the membrane surface, play an anti-pollution role, and enable the piezoelectric SiC ceramic membrane to have an in-situ self-cleaning function.
[0085] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention fall within the scope of protection of the present invention.
Claims
1. A piezoelectric SiC ceramic membrane with in-situ self-cleaning function, characterized in that: The method uses SiC ceramic membrane as a base membrane and is composed of a base membrane and UiO-66-NH2(Hf) loaded on the base membrane.
2. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 1, characterized in that: In the piezoelectric SiC ceramic film, the loading amount of UiO-66-NH2(Hf) is 65.12-86.15 g / m 2 .
3. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 1, characterized in that: The base film is a SiC ceramic film modified with hydroxyl functional groups, and the SiC ceramic film modified with hydroxyl functional groups is obtained by sequentially subjecting a clean SiC ceramic membrane to oxidation treatment and acidification treatment.
4. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 3, characterized in that: The preparation of the SiC ceramic membrane modified with hydroxyl functional groups comprises the following operations: First, the SiC ceramic diaphragm is cleaned and dried to obtain a clean SiC ceramic diaphragm; then, the clean SiC ceramic diaphragm is oxidized in air or oxygen atmosphere to obtain a slightly oxidized diaphragm; then, the slightly oxidized diaphragm is placed in a strong acid solution for acidification treatment, and finally, the diaphragm is taken out, cleaned, and dried to obtain a SiC ceramic membrane modified with hydroxyl functional groups.
5. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 4, characterized in that: The oxidation treatment refers to placing a clean SiC ceramic diaphragm in a muffle furnace and performing oxidation treatment at 900°C to 1200°C for 60 to 150 minutes in air or oxygen atmosphere to obtain the micro-oxidation diaphragm.
6. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 4, characterized in that: The acid treatment refers to soaking the micro-oxidation membrane in a strong acid solution for 20 to 30 hours, taking out the membrane, washing the membrane with deionized water until it is neutral, and drying to obtain the SiC ceramic membrane modified with hydroxyl functional groups, wherein the strong acid solution is a mixed solution of concentrated hydrochloric acid: concentrated nitric acid in a volume ratio of (8 to 12):
1.
7. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 1, characterized in that: The piezoelectric SiC ceramic film is obtained by subjecting a base film and a crystal growth solution to a hydrothermal reaction, and loading UiO-66-NH2(Hf) on the base film through a hydrothermal method.
8. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 7, characterized in that: The piezoelectric SiC ceramic film is obtained by loading UiO-66-NH2(Hf) on the base film by a hydrothermal method, including the following operations: a) preparing a primary crystal growth solution of hafnium chloride: 2-aminoterephthalic acid: N,N-dimethylformamide: water: acetic acid = 1:1:500:10:1, placing a base film in the primary crystal growth solution, reacting at 110° C. to 130° C. for 12 to 24 hours, and after the reaction is completed, taking out the film, washing it, and drying it to obtain a primary loaded film; b) hafnium chloride: 2-aminoterephthalic acid: N,N-dimethylformamide: water: acetic acid are prepared into a secondary crystal growth solution according to a molar ratio of (1-2): (1-2): 500:10:1, the prepared primary load membrane is placed in the secondary crystal growth solution, and reacted at 110°C to 130°C for 20 to 30 hours. After the reaction is completed, the membrane is taken out, cleaned and dried to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
9. The piezoelectric SiC ceramic film with in-situ self-cleaning function according to claim 8, characterized in that: In step a), after the reaction is completed, the membrane is taken out, first washed with N, N-dimethylformamide solution, then washed with anhydrous ethanol, and then vacuum dried at 60°C to 100°C to obtain the primary loaded membrane; in step b), after the reaction is completed, the membrane is taken out, first placed in a mixed solution of N, N-dimethylformamide: concentrated hydrochloric acid with a volume ratio of (30 to 50):1, soaked at 60°C to 100°C for 8 to 12 hours, then taken out, and then soaked and cleaned with ethanol solution, and finally vacuum dried at 60°C to 100°C to obtain the piezoelectric SiC ceramic membrane with in-situ self-cleaning function.
10. Application of the piezoelectric SiC ceramic membrane with in-situ self-cleaning function in oil-water separation as claimed in claim 1, characterized in that: The following operations are included: First, a piezoelectric SiC ceramic membrane is placed in a filter tank as a filter membrane; then, oily wastewater containing emulsified oil with an initial turbidity of C0 is passed into the filter tank. During the process of passing the oily wastewater into the filter tank, the hydraulic pressure of the oily wastewater is first quickly increased from 0 bar to 2 bar within 1 to 3 seconds, and then the hydraulic pressure is maintained at 2 bar for 50 to 70 seconds, and then the hydraulic pressure is returned to 0 bar within 1 to 3 seconds, and thus, a periodic cycle is performed in a mode of pressure increase, pressure maintenance, and pressure reduction; the oily wastewater is filtered through the filter membrane, and the turbidity of the obtained filtrate is detected by a turbidity meter to obtain the turbidity C1 of the oily wastewater after membrane separation; then, the retention rate R of the filter membrane for the oily wastewater is calculated according to the formula R=((C0-C1) / C0)×100%.
Citation Information
Cited By
Control circuit of equipment for preparing double electrolyzed water based on O3 and H2O2 in parallel and control method thereof
CN119937437A
Piezocatalytic ceramic composite membrane, preparation method and application thereof
CN122937661A
